Acute kidney injury after associating liver partition and portal vein ligation for staged hepatectomy for hepatocellular carcinoma: two case reports and a literature review - Huang, Hanchun (Ann Transl Med, 2019)
Associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) is used for avoiding postoperative live failure caused by insufficient future liver remnant (FLR) after major liver resection. However, ALPPS accompanied by high morbidity and mortality. The surgeons focus their attention mainly on the common complications such as bile leak, bleeding, infection and liver failure. Acute kidney injury (AKI) is a relatively rare postoperative complication, and get less attention. However, once AKI occurred after the surgery, it will seriously affect the prognosis of patients. We firstly report two cases of postoperative AKI after ALPPS in hepatocellular carcinoma with liver cirrhosis. Case 1, a 61-year-old male, chief complaint upper abdominal pain for half a month, medical examination found a huge liver space-occupying lesion. The clinical diagnosis was liver cancer, and ALPPS was performed. After the first step of surgery, delayed renal replacement therapy (RRT) was initiated when stage 3 AKI diagnosed. Although the second step surgery completed successfully, the patient eventually died of multiple organ dysfunction syndrome (MODS) induced by gastrointestinal bleeding. Case 2, a 64-year-old male chief complaint right liver mass present to our hospital, with a small FLR. Stage 2 AKI was diagnosed after the first step of ALPPS, early RRT was started immediately. Renal function gradually recovered, and the second step surgery was completed. The patient discharged with a good condition, found no recurrence in the latest follow-up. ALPPS for hepatocellular carcinoma with liver cirrhosis cases, more likely to happen AKI. More strict patient screening criteria, early RRT may improve the prognosis.